Estimating Unsaturated Hydraulic Conductivity in Unsaturated Soil Using Soil Moisture Sensors - Ong, Sin Tian; Giap, Goh Eng; Rudiyanto; Mohammad Fadhli Ahmad; Abdul Aziz, Roslaili (International Journal of Integrated Engineering, 2023)
Unsaturated hydraulic conductivity (K) is a measurement of soil water-retaining ability in unsaturated soil. The unsaturated hydraulic properties are necessary to predict the movement of water in unsaturated soil. The current study aims to create an alternative experimental device to estimate the unsaturated hydraulic conductivity (K) using water sensors. The experimental set up was designed and fabricated in order to measure the volumetric water content using GS3 (Campbell) sensors at different heights. The data obtained from the sensors was validated using mass of moist sand column measured from electronic balance. The unsaturated hydraulic conductivity (K) was estimated with the help of retention and conductivity functions. The primary materials used in the study were solute-free water and sand. It was found that the reading from the sensors was in good match with the reading of the volumetric water content calculated from the mass of water in the sand column with a root mean square error of 0.0091. Soil water retention curve and hydraulic conductivity were plotted using Peters-Durner-Iden (PDI) model. The current experimental set up required approximately up to 4-5 months of open drying to adequately estimate unsaturated hydraulic conductivity in a dry soil region.